Cognitive Anxiety and Habits of Mind: A Study of the Interrelationships with Biology Learning Outcomes - Ilma Riksa Isfiani; Bambang Ekanara (Scientiae Educatia: Jurnal Pendidikan Sains, 2022)
Biology learning outcomes are related to several factors, namely cognitive anxiety and habits of mind. The purpose of this study is to analyze the relationship between cognitive anxiety, habits of mind, and biology learning outcomes. The method of research applied  was correlational research with a stratified random sampling technique. The population of this study is all class XII students at four senior high schools in Bandung with a total sample of 145 students. The instruments used were questionnaires and Biology study results report documents. Habits of mind in this study refer to Costa and Kallick’s 16 categories of habits of mind as many as 50 questionnaire coverage. Students' cognitive anxiety was measured through a cognitive anxiety questionnaire which consists of 27 statement items based on Cassady and Johnson's Cognitive Anxiety Test. The learning outcomes were obtained from the scores of grade XII National Exam Practice. The instruments were tested for validity, reliability, and readability. It was found that there was a positive relationship between biology learning outcomes and cognitive anxiety (r = 0,045, α <0.025 ) as well as between habits of mind and biology learning outcomes (r= 0,326, α <0.025). No correlation was observed between habits of mind and cognitive anxiety. It can be summarized that habits of mind and cognitive anxiety have a positive relationship with biology learning outcomes. These findings indicate that biology learning outcomes are closely related to cognitive anxiety and habits of mind. Finally, we discuss the relationship of cognitive anxiety and the habits of mind to biology learning outcomes and provide suggestions for further work.